Thickness Influence on Structural and Optical Properties of ZnO Thin Films Prepared by Thermal Evaporation - A. maki, Samir; H. shaban, Auday; A. hussain, Shahd (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
A thermal evaporation technique was used to prepare ZnO thin films. The samples were prepared with good quality onto a glass substrate and using Zn metal. The thickness varied from (100 to 300) Â±10 nm. The structure and optical properties of the ZnO thin films were studied. The results of XRD spectra confirm that the thin films grown by this technique have hexagonal wurtzite, and also aproved that ZnO films have a polycrystalline structure. UV-Vis measurement, optical transmittance spectra, showed high transmission about 90% within visible and infrared range. The energy gap is found to be between 3.26 and 3.14e.V for 100 to 300 nm thickness respectivly. Atomic Force Microscope AFM (topographic image ) shows the grain size increased in the range (91.29 -110.11)nm.